Bovine leukemia virus can be classified into seven genotypes: evidence for the existence of two novel clades - Rodriguez, Sabrina M.; Golemba, Marcelo D.; Campos, Rodolfo H.; Trono, Karina; Jones, Leandro R. (Journal of General Virology, 2009)
Previous studies have classified the env sequences of bovine leukemia virus (BLV) provirus from different locations worldwide into between two and four genetic groupings. These different studies gave unique names to the identified groups and no study has yet integrated all the available sequences. Thus, we hypothesized that many of the different groups previously identified actually correspond to a limited group of genotypes that are unevenly distributed worldwide. To examine this hypothesis, we sequenced the env gene from 28 BLV field strains and compared these sequences to 46 env sequences that represent all the genetic groupings already identified. By using phylogenetic analyses, we recovered six clades, or genotypes, that we have called genotypes 1, 2, 3, 4, 5 and 6. Genotypes 1–5 have counterparts among the sequence groupings identified previously. One env sequence did not cluster with any of the others and was highly divergent when compared with the six genotypes identified here. Thus, an extra genotype, which we named 7, may exist. Similarity comparisons were highly congruent with phylogenetic analyses. Furthermore, our analyses confirmed the existence of geographical clusters.